2022
DOI: 10.1038/s41598-022-06334-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and underlying mechanism of autophagy-related genes in bladder cancer

Abstract: Bladder cancer (BLCA) is the most common malignancy whose early diagnosis can ensure a better prognosis. However, the predictive accuracy of commonly used predictors, including patients’ general condition, histological grade, and pathological stage, is insufficient to identify the patients who need invasive treatment. Autophagy is regarded as a vital factor in maintaining mitochondrial function and energy homeostasis in cancer cells. Whether autophagy-related genes (ARGs) can predict the prognosis of BLCA pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previous researchers have constructed a prediction model for BLCA prognosis based on the TCGA-BLCA dataset. For example, Peng et al [35] developed a prognostic model based on five autophagy-related genes, and its AUC value was 0.724. Zhang et al [36] constructed a prognostic model based on five pyroptosisrelated genes, and the AUCs of the 5-gene model for 1-, 3-, and 5-year OS were 0.667, 0.632, and 0.637, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers have constructed a prediction model for BLCA prognosis based on the TCGA-BLCA dataset. For example, Peng et al [35] developed a prognostic model based on five autophagy-related genes, and its AUC value was 0.724. Zhang et al [36] constructed a prognostic model based on five pyroptosisrelated genes, and the AUCs of the 5-gene model for 1-, 3-, and 5-year OS were 0.667, 0.632, and 0.637, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peng et al . [ 35 ] developed a prognostic model based on five autophagy‐related genes, and its AUC value was 0.724. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…As for the causes of gender differences in bladder cancer incidence, the current study indicated that the higher incidence among men may be due to their more frequent exposure to toxic substances, smoking, long-term drinking, and other reasons, but there are few studies on genetic differences in males and females. Currently, there are several reports on the role of immune cell in ltration-related genes [19], pyroptosis-related genes [20], and autophagy-related genes [21], in the development of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%